CHINESE POSTPARTUM PRACTICES IN CONFINEMENT CENTRES IN IPOH, PERAK : THE SIGNIFICANCE ON MOTHER AND NEWBORN - Hee, Kai Qi (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The Chinese postpartum or known as 坐月子 (pinyin : Zuo Yue Zi ; Doing the month) required women to confine at home for a month for recovery after childbirth. The aim of this study is to discover the Chinese postpartum that practising in confinement centres within the area of Ipoh, Perak. Structural Functionalism Approach is used in order to explore the function of services that offer by the confinement centres. The discussion and analysis are categorises into the significances of confinement centre and postnatal taboo, the function of aids and impact of the shift of trend. Although the Chinese postpartum practices have become an alternative instead of dominant practices due to the influences of globalization and modernization. But, the practices still practices and become commercialized until present due to the value of adaptability and functionality.